Community-based culinary and nutrition education intervention promotes fruit and vegetable consumption. Issue 2 (6th February 2022) - Metcalfe, Jessica Jarick; Prescott, Melissa Pflugh; Schumacher, Melissa; Kownacki, Caitlin; McCaffrey, Jennifer
Abstract: Objective: The main objective of this study was to evaluate the impact of the Market to MyPlate (M2MP) program on fruit and vegetable consumption and cooking behaviours. Secondary objectives were to examine factors that affected participant retention and program completion, and analyse program feedback provided by participants. Design: This study conducted a mixed methods evaluation embedded within a cluster randomised controlled trial of the M2MP intervention. Adult participants completed a pre- and post-program survey reporting on their fruit and vegetable consumption and cooking behaviours. A subsample participated in structured interviews, providing feedback about M2MP and the impact of the program. Setting: Seven weekly classes took place in community centres and extension offices in central Illinois. Participants: 120 adults and their families participated. Class cohorts were randomly assigned to one of three treatment groups: (1) nutrition education and cooking classes with produce allocations (PAE, n 39); (2) nutrition education and cooking classes only (EO, n 36) or (3) control group ( n 45). Results: Compared to control, PAE participants reported larger increases from pre- to post-intervention in fruit ( P = 0·001) and vegetable consumption ( P = 0·002), with no differences in cooking frequency. Interview analyses identified key themes in behaviour changes due to M2MP, including reported increases in dietary variety, cooking self-efficacy and children's participation in cooking. Conclusions: PAE participants who received an intervention that directly increased their access to fresh produce (via produce allocations) increased their reported fruit and vegetable consumption. Though participants' cooking frequency did not change, interviewees reported increased variety, cooking confidence and family participation in cooking.